Comparison of Goldmann applanation, non-contact, dynamic contour and tonopen tonometry measurements in healthy and glaucomatous eyes, and effect of central corneal thickness on the measurement results - Aydın Yildiz; Tekin Yasar (Medicinski glasnik, 2018)
Aim: To compare the correlation of intraocular pressure (IOP) measurements obtained using Goldmann applanation tonometry (GAT), non-contact tonometry (NCT), dynamic contour tonometer (DCT) and tono-pen (TP) in glaucomatous and healthy eyes, and to investigate the effect of central corneal thickness (CCT) on the measurements. Methods: One hundred eyes of 100 glaucoma patients and 50 eyes of 50 healthy individuals were compared. In all of the eyes, CCT was evaluated using ultrasonic pachymeter. IOP was measured using NCT, TP, DCT and GAT, respectively. IOP measurements and correlation of these measurements with CCT were calculated using Pearson and intra-group correlation analysis. Results: In the glaucoma group, the mean IOP was 16.42 ± 2.80 mmHg with NCT, 17.12 ± 2.49 mmHg with TP, 18.27 ± 2.62 mmHg with DCT and 16.08 ± 3.00 mmHg with GAT. The mean CCT was 532.15 ± 39.08 ?m. In normal individuals, mean IOP was 14.64 ± 2.20 mmHg with NCT, 15.32 ± 1.85 mmHg with TP, 16.72 ± 2.31 mmHg with DCT and 14.16 ± 2.80 mmHg with GAT. The mean CCT was 538.40 ± 31.64 ?m. Conclusion: A strong compliance between NCT and GAT has been observed. NCT can be used instead of GAT.
Keywords: intraocular pressure; glaucoma; cornea; tonometer; pachymeter